Temporal, climatic and spatial variation in the distribution and activity patterns of the raccoon (Procyon lotor) in Hainich National Park, Germany - Grüneberger, Maria (2022)
The raccoon (Procyon lotor) has been a part of German fauna since the 1920s, following a number of releases and escapes from captivity. This study intends to investigate the distribution and activity patterns of this non-native mesopredator in Hainich National Park, which lies in Central Germany, in-between 3 core areas of established raccoon populations. I analysed metadata from over 12,000 camera trap pictures of raccoons, which were sampled by 120 camera traps distributed over Hainich National Park. I compared this to meteorological data covering the same area and spatial variables within a 4-km-buffer around the National Park. The study period covered winter and early spring during each of the 3 consecutive years 2017 to 2019. A total of 2,300 raccoons were recorded by all camera traps across all study periods during 2,095 trigger events. Being highly mobile, the large majority of raccoons stayed not even one minute inside the camera frame. Over 99 % of recordings showed adults which might be explained by the study periods being temporally placed in-between reproductive cycles. Raccoons, both in their native and their new range, are known to be nocturnal animals, thus it was predictable that they were significantly more active during the night, defined as the period between one hour after sunset until one hour before sunrise. Activity during the rest of the day, especially during dusk, increased steadily with each month of the study period. General raccoon activity followed the same pattern until a sudden decrease in April. Ground temperature was the only climate variable for which a significant (positive) correlation could be shown. This was in accordance with studies on original and new raccoon range expansion. However, a dormant period, as shown for raccoons in a similar habitat in Germany, could not be seen. Habitat preferences differed depending on the testing method: A considerable proportion of raccoons were sampled in mixed deciduous forest, while most raccoons per camera were sampled in mixed coniferous forest. Duncan’s index of habitat preference points to a preference of mixed coniferous forest as well, and literature argues in favour of mixed deciduous forest where raccoons find important resources such as shelter in European beeches. Regarding the geographical distribution over Hainich National Park, raccoons were mainly sampled close to the border, to hiking and biking trails and to anthropogenic structures, especially the visitor magnet Canopy Walk, presumably for complementing their diet with crops from nearby fields and scavenged trash. I conclude that the raccoon is an opportunistic generalist that thrives in Hainich National Park, though more studies are needed to understand the species’ ecology in its new habitat.